Social Awareness and Use of Face Masks among Medical Students in Association with the COVID-19 Pandemic - Islam, Md Serajul; Islam, Mir Moyeedul; Nazneen, Nazia; Zaman, Tamrin (Community Based Medical Journal, 2024)
A cross-sectional, descriptive study was conducted to assess the level of social awareness and use of face mask in association with the COVID-19 pandemic among the medical students of Ad-din Sakina Women’s Medical College, Jashore, Bangladesh, between January and February of 2022. The study was carried out in the Department of Community Medicine. A total of 354 students of the same medical college participated in the survey. Data was collected by structured questionnaire and data processing and statistical analysis were done by using SPSS version 25.0. The age of the respondents was between 18 and 26 years. The mean age was 21.73 years. 82.8% of respondents were Muslims and 15.3% were Hindu. The average monthly family income of respondents was about 53,000 BDT. 83% of the respondents used face masks for the protection against COVID-19. 70.3% of the respondents relied more on the surgical type of mask. According to the survey the main mode of transmission of virus was found to be through respiratory droplets by 87.3% of the respondents. However, 13% failed to recognize droplet inhalation as a source of transmission. 92.1% of the respondents believed that the route of transmission includes eyes, nose, and mouth. Among the respondents 96% sanitize hand and face properly and 87.3% maintain social distance. It was found out that 7.1 percent of the respondents were affected by COVID-19 and 100% respondents were vaccinated against COVID-19. These findings clearly showed a satisfactory level of awareness and attitudes among the medical students towards COVID-19. Promoting the use of facemasks and educating the public about mask-wearing as an effective tool in disease prevention may also help to increase the public’s perceived benefits, which may then also contribute to increasing mask-wearing compliance. Facemasks play a pivotal role in the prevention and control of infectious respiratory disease transmission. CBMJ 2024 January: vol. 13 no. 01 P: 71-76